2017
DOI: 10.1128/jcm.00775-17
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenemase Detection among Carbapenem-Resistant Glucose-Nonfermenting Gram-Negative Bacilli

Abstract: Accurate detection of carbapenemase-producing glucose-nonfermenting Gram-negative bacilli (CPNFs), including Pseudomonas aeruginosa and Acinetobacter baumannii, is necessary to prevent their dissemination within health care settings. We performed a method comparison study of 11 phenotypic carbapenemase detection assays to evaluate their accuracy for the detection of CPNFs. A total of 96 carbapenem-resistant glucose-nonfermenting isolates were included, of which 29% produced carbapenemases. All CPNFs were molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 21 publications
(21 reference statements)
2
31
0
Order By: Relevance
“…However, the increased sensitivity (60% to 93%) was at the expense of specificity, as was observed with A. baumannii isolates, where the specificity decreased from 100% using a 1-l loop to 63% using a 10-l loop (33). Others have found similar limitations with the performance of the mCIM in detecting carbapenemase-producing A. baumannii strains (34). The 28th edition of the CLSI M100 supplement document endorses the use of the mCIM using a 10-l inoculum for the detection of carbapenemase production among carbapenem-resistant P. aeruginosa strains (7).…”
Section: Overview Of Phenotypic Assaysmentioning
confidence: 71%
See 1 more Smart Citation
“…However, the increased sensitivity (60% to 93%) was at the expense of specificity, as was observed with A. baumannii isolates, where the specificity decreased from 100% using a 1-l loop to 63% using a 10-l loop (33). Others have found similar limitations with the performance of the mCIM in detecting carbapenemase-producing A. baumannii strains (34). The 28th edition of the CLSI M100 supplement document endorses the use of the mCIM using a 10-l inoculum for the detection of carbapenemase production among carbapenem-resistant P. aeruginosa strains (7).…”
Section: Overview Of Phenotypic Assaysmentioning
confidence: 71%
“…The modified Carba NP test increases the ability to detect carbapenemase production in A. baumannii but remains suboptimal. In one study, the sensitivities of the CLSI Carba NP and modified Carba NP test were 21% (95% CI, 6 to 51%) and 79% (95% CI, 49 to 94%), respectively (34).…”
Section: Overview Of Phenotypic Assaysmentioning
confidence: 99%
“…We found that an increased inoculum was required for the mCIM for reliable detection of carbapenemase production among these nonfermenters compared to among the Enterobacteriaceae, as some VIM-producing P. aeruginosa and many acquired-OXA-CHDLproducing A. baumannii strains were not consistently detected using a 1-l loopful of organism. Thus, we performed a multisite study of the mCIM at 10 testing sites as previously described, with the exception that a 10-l loopful of organism was used for setup (7). Overall, the mean sensitivity, specificity, and kappa coefficient for detection of CP-PA isolates across all sites were 98.0% (95% CI, 94.3 to 99.6; range, 86.7 to 100), 95% (95% CI, 89.8 to 97.7; range, 93.3 to 100), and 0.94, respectively, whereas the mean sensitivity, specificity, and kappa coefficient among CP-AB isolates were 79.8% (95% CI, 74.0 to 84.9; range, 36.3 to 95.7), 52.9% (95% CI, 40.6 to 64.9; range, 28.6 to 100), and 0.56, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Many phenotypic methods for detection of carbapenemase producers have been described for the Enterobacteriaceae, some of which can be applied to the nonfermenters, such as P. aeruginosa and A. baumannii (2,7). Phenotypic methods defined by the Clinical and Laboratory Standards Institute (CLSI) that clinical microbiology laboratories can apply to detect carbapenemase producers include the modified Hodge test (to be removed from the M100 in 2018; CLSI, January 2017 meeting minutes), the Carba NP test, and most recently the modified carbapenem inactivation method (mCIM) (8,9).…”
mentioning
confidence: 99%
“…The Clinical and Laboratory Standards Institute (CLSI) now recommends the mCIM, a modified carbapenem inactivation method, for the detection of carbapenemase activity in Enterobacteriaceae (7). The mCIM has greater sensitivity than the CIM in detecting carbapenemase production in Enterobacteriaceae (8) and in glucose-nonfermenting Gram-negative bacteria (9). However, the ability of the mCIM to detect carbapenemase production in certain Gram-negative bacteria can be improved.…”
mentioning
confidence: 99%